ANALYSIS OF FACTORS AFFECTING CHANGES IN JCI VALUE ON THE INDONESIA STOCK EXCHANGE - Alamsyah Noval Mahardika; Whinarko Juliprijanto (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
This research aims empirical evidence regarding the impact of the inflation rate, the BI Rate, the dollar exchange rate, and the interest rate on the Composite Stock Price Index (JCI). Composite Stock Price Index (JCI) is one of the indexes that investors frequently consider when making investments on the Indonesia Stock Exchange. Therefore, the authors wish to investigate the factors that influence the CSPI in greater detail. This study's population comprises the overall annual data for the inflation rate, BI Rate, Exchange Rate, and Composite Stock Price Index (JCI) from 1991 to 2020. The sampling method employed is a saturated sample in which the entire population is represented. This study employs the ECM technique. The results indicated that the inflation rate, the BI Rate, and the Dollar Exchange Rate (USD/IDR) partially influenced the Composite Stock Price Index (JCI).